Outdoor fungi and child asthma health service attendances. Issue 5 (August 2014) - Tham, Rachel; Dharmage, Shyamali C.; Taylor, Philip E.; Katelaris, Constance H.; Vicendese, Don; Abramson, Michael J.; Erbas, Bircan
Abstract Asthma is a significant global public health issue. Severe asthma exacerbations can be triggered by environmental factors and require medical care from health services. Although it is known that fungal exposure may lead to allergic sensitization, little is understood about its impact on asthma exacerbations. This review aims to examine whether outdoor fungi play a significant role in child asthma exacerbations. Systematic search of seven electronic databases and hand searching for peer‐reviewed studies published in English, up to 31 August 2013. Inclusion criteria were study population aged <18 yr, diagnosis of asthma, attended a health service; outdoor fungi exposure was reported. Quality and risk of bias assessments were conducted. Due to significant heterogeneity, meta‐analysis was not conducted. Of the 1896 articles found, 15 were eligible. Findings were not consistent, possibly due to methodological variations in exposure classifications, statistical methods and inclusion of confounders. Cross‐sectional studies found no or weak associations. All but one time series studies indicated an association that varied between fungal species. Increasing evidence indicates that asthmatic children are susceptible to asthma exacerbations when exposed to outdoor fungal spores. There is limited understanding of the contributions of different fungal species. Research is needed to investigate interactions of outdoor fungi with pollen, air pollutants and respiratory viruses.